If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3e + -9 = 3 Reorder the terms: -9 + 3e = 3 Solving -9 + 3e = 3 Solving for variable 'e'. Move all terms containing e to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + 3e = 3 + 9 Combine like terms: -9 + 9 = 0 0 + 3e = 3 + 9 3e = 3 + 9 Combine like terms: 3 + 9 = 12 3e = 12 Divide each side by '3'. e = 4 Simplifying e = 4
| 8u+46=6(u+9) | | 5ab-3bc= | | (2q-3)-(q-4)=18 | | -8(2t+4)=-64 | | t-7t= | | -3(u-1)=-6u+21 | | 3ab+4cd= | | 6x-18=5x+5 | | -15/7-11/5 | | y=-9.8x^2+34.3x+2.1 | | (-15/7-11/5)*5.6 | | 4m-6mp= | | 5x^2-13x+5=0 | | (-(15/7)-(11/5))*5.6 | | y=5x+8whatisb | | 5m+2mp= | | 61-((126/(9/((76/4)-16)))/3) | | .0015x^2-.141x+26.3=.0014X^2-.1148X+22.4 | | 61-((126/(9/((76/4)-16)))/3 | | 8pt+5ab= | | (-(2*1/7)-(2*1/5))*5.6 | | (z-17)*4=36 | | 5100=.9*X | | 7m-6t= | | 5.6*(-(2*1/7)-(2*1/5)) | | x=5100*.9 | | 5.6*(-(2*1/7)-(3-((2*3)/7)) | | 10pt+15pt+5pt= | | 5.6*(-(2*1/7)*(3-((2*3)/7)) | | 5t+4t+at= | | -2(2t+1)=-14 | | 2-(18/q^2)=0 |